CONDUCTING INTERORGANIZATIONAL RESEARCH USING KEY INFORMANTS. - KUMAR, N.; STERN, L. W.; ANDERSON, J. C. (Academy of Management Journal, 1993)
Your use of the JSTOR archive indicates your acceptance of JSTOR's Terms and Conditions of Use, available at